2021
DOI: 10.1021/acs.macromol.1c01098
|View full text |Cite
|
Sign up to set email alerts
|

High Toughness Polyurethane toward Artificial Muscles, Tuned by Mixing Dynamic Hard Domains

Abstract: Developing multiphase polyurethanes (PUs) with loosely packed domains containing dynamic linkages and appropriately crystallized soft phases composed of polycaprolactone diol (PCL) segments is effective for the trade-off between toughness and self-healing. Here, we proposed a new strategy based on mixed dynamic hard segments to achieve the goal and improve self-healing behavior and mechanical performance. The designed polyurethanes comprise a microphase-separated structure with polycaprolactone diol as soft se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…It has been experimentally and theoretically demonstrated that the hydrogen bonds between urea linkages are the primary force for microphase separation, motivating the stacking of hard segments to form hard microphases and having a significant impact on the macroscopic properties of the material as physical cross‐linking 16–18 . We could thus investigate the stacking of hard domains by observing the strength of hydrogen bonding in SPU samples with different APD content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been experimentally and theoretically demonstrated that the hydrogen bonds between urea linkages are the primary force for microphase separation, motivating the stacking of hard segments to form hard microphases and having a significant impact on the macroscopic properties of the material as physical cross‐linking 16–18 . We could thus investigate the stacking of hard domains by observing the strength of hydrogen bonding in SPU samples with different APD content.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peak of “Free” CO groups without hydrogen bonding corresponds to the highest wavenumbers. Once the hydrogen bonds form, the bond distance of CO is elongated and the bonding force is weakened, which lead to the decrease of the stretching vibration frequency and eventually cause the position of CO vibration band to shift toward the low wavenumber 17 . “Disordered” CO groups shift to lower wavenumbers due to distribution of electrons for two‐dimensional structure of single ligand, while “Ordered” CO shift to the lowest wavenumbers for the three‐dimensional structure of bidentate ligand 4,16,19 .…”
Section: Resultsmentioning
confidence: 99%
“…1 The hard domains of TPU could be formed based on different interactions such as π−π stacking and hydrogen bonds (H-bonds). 2,3 The soft segments are often composed of supple alkyl long chains. Therefore, TPU tends to exhibit a multiphase separation structure owing to the thermodynamic incompatibility between soft and hard segments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) elastomer, as a kind of block copolymer which consists of alternate soft and hard segments, is extensively investigated because of the flexible design of its molecular structure and stable mechanical properties . The hard domains of TPU could be formed based on different interactions such as π–π stacking and hydrogen bonds (H-bonds). , The soft segments are often composed of supple alkyl long chains. Therefore, TPU tends to exhibit a multiphase separation structure owing to the thermodynamic incompatibility between soft and hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic isocyanate bands, which are -N = C = O asymmetric stretch at 2272 cm − 1 and symmetric stretch at 1443 cm − 1 are absent in the spectrum as an indication of complete consumption of the functionality. Based on the images, the polyurethane bands are as follows: -NH-(amide I 1732 cm − 1 , amide II 1530 cm − 1 , amide III 1303 cm − 1 ), Ester υ(C = O) (urethane amide I υ(C = O) 1732 cm − 1 , δ(CH 2 ) :1443 cm − 1 and δ(CH) (urethane amide III 1249)(Ha et al, 2019;Qu et al, 2021). The band related to the ester carbonyl group is not available in the Raman spectrum of the PTMG-tPU and its intensity for the other three tPU specimens is lower than that of PCL-tPU.…”
mentioning
confidence: 99%